Peran Psikolog dalam Bidang Pendidikan, Pemerintahan dan Industri - Muhamad Uyun (Psympathic: Jurnal Ilmiah Psikologi)
The purposes of this research were to find out the roles of psychologists in the scope of education, government and industry. The research used qualitative method and the data collection technique was interview. The key informants in all fields totaling 9 informants were selected by purposive sampling. The results of the study of the roles of psychologists in the field of education actualize the right action in the interaction between each educational factor especially on student acceptance, diversity of students, determining learning strategies and methods, conducting guidance and briefing as well as evaluating results. Furthermore, the roles of the psychologists in the field of government were to create a clean government, good integrity, professional and transparency. Lastly, the role of psychologists in industrial field were related to the development, maintenance and work productivity of employees as well as evaluating prospective employees.